Understanding decision making about major surgery: protocol for a qualitative study of shared decision making by high-risk patients and their clinical teams. Issue 5 (5th May 2020) - Shaw, Sara; Hughes, Gemma; Stephens, Tim; Pearse, Rupert; Prowle, John; Ashcroft, Richard Edmund; Avagliano, Ester; Day, James; Edsell, Mark; Edwards, Jennifer; Everest, Leslie
Abstract : Introduction: Surgical treatments are being offered to more patients than ever before, and increasingly to high-risk patients (typically multimorbid and over 75). Shared decision making is seen as essential practice. However, little is currently known about what 'good' shared decision making involves nor how it applies in the context of surgery for high-risk patients. This new study aims to identify how high-risk patients, their families and clinical teams negotiate decision making for major surgery. Methods and analysis: Focusing on major joint replacement, colorectal and cardiac surgery, we use qualitative methods to explore how patients, their families and clinicians negotiate decision making (including interactional, communicative and informational aspects and the extent to which these are perceived as shared) and reflect back on the decisions they made. Phase 1 involves video recording 15 decision making encounters about major surgery between patients, their carers/families and clinicians; followed by up to 90 interviews (with the same patient, carer and clinician participants) immediately after a decision has been made and again 3–6 months later. Phase 2 involves focus groups with a wider group of (up to 90) patients and (up to 30) clinicians to test out emerging findings and inform development of shared decision making scenarios (3–5 summary descriptions of how decisions are made). Ethics and dissemination: The study forms the first part in a 6-year programme of research, Optimising Shared decision-makIng for high-RIsk major Surgery (OSIRIS). Ethical challenges around involving patients at a challenging time in their lives will be overseen by the programme steering committee, which includes strong patient representation and a lay chair. In addition to academic outputs, we will produce a typology of decision making scenarios for major surgery to feed back to patients, professionals and service providers and inform subsequent work in the OSIRIS programme.